2018
DOI: 10.1016/j.childyouth.2018.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Defining and achieving permanency among older youth in foster care

Abstract: Permanency is a key child welfare system goal for the children they serve. This study addresses three key research questions: (1) How do older youth in foster care define their personal permanency goals? (2) How much progress have these youth made in achieving their personal permanency goals and other aspects of relational permanency, and how does this vary by gender, race, and age? and (3) What transition-related outcomes are associated with relational permanency achievement? Surveys were conducted with 97 yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…These young people value many aspects of the relationships with these caring adults (e.g., how they provide a safe space, emotional support, and guidance) and highlight the importance of consistent involvement (Kothari et al, 2020). In fact, some studies have revealed that relational permanency appears to be what matters most for these young people (Salazar et al, 2018). It is necessary, therefore, to understand the ways in which youth–foster caregiver relationships may help facilitate positive educational outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These young people value many aspects of the relationships with these caring adults (e.g., how they provide a safe space, emotional support, and guidance) and highlight the importance of consistent involvement (Kothari et al, 2020). In fact, some studies have revealed that relational permanency appears to be what matters most for these young people (Salazar et al, 2018). It is necessary, therefore, to understand the ways in which youth–foster caregiver relationships may help facilitate positive educational outcomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At its core, permanency is about 'securing the right placement for the right child at the right time' (Boddy, 2013, p. 1). In this sense, Sinclair (2005), Sinclair et al, (2007), Biehal et al, (2012), Schofield and Simmonds (2011) and Salazar et al, (2018) emphasise the importance of permanency providing a child with stability, emotional constancy and solidity. For a child to feel a sense of permanency therefore, their living arrangements need to be characterised by balanced emotional attachments to adults and siblings and a feeling that they are part of a family (Salazar, 2012;2013).…”
Section: Placement Options For Children Looked After By Local Authoritiesmentioning
confidence: 99%
“…MacDonald defines permanence as 'a sense of security, continuity, commitment, and identity throughout childhood and beyond ' (2016, p. 3). Recently, Salazar et al (2018) defines permanence as 'ensuring that children and youth having meaningful, enduring connections to a family or other long-term caring adults' and as 'legal status'.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main intrinsic factors are summarised as: mental health status (Salazar et al, 2018); behavioural and emotional development; age at entry to care (Ibid); confidence and selfidentity; school experiences; and prior experiences of trauma, abuse, and neglect (Metzler et al, 2017). The main extrinsic factors include the number of placement moves stability in the family structure, the foster carer's ability to cope and their resources, the level of alignment in expectations of the foster family, relationships with families of origin, relationships with foster siblings and relationships with social workers (Wojciak et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%